Construction and Demolition Waste: Challenges and Opportunities - Maury-Ramirez, Anibal C.; Mesa, Jaime A (2022)
The current production and consumption models of building materials are causing severe environmental and social problems worldwide. In this sense, construction and demolition waste (C&DW) are part of the problem and can be part of the solution, particularly in developing countries where the construction industry is growing very rapidly. Although many efforts have been made by stakeholders to increase the use of C&DW in construction materials, articulated efforts are required at global, national, and local scales to develop truly sustainable construction sectors. Therefore, this e-book, which is based on the "Special Issue on Construction and Demolition Waste: Challenges and Opportunities", is an effort to articulate knowledge on novel and innovative building materials using C&DW and management systems to develop circular economy models (CE) for the construction sector. In this e-book, it is concluded that even though the valorization of C&DW has been developed worldwide, more incentives need to be provided to really convert the local and national construction chains in sustainable sectors, which appropriate the circular economy for production and consumption systems that imrpove, at the least, efficiency in terms of materials, water and energy use.